2021
DOI: 10.1177/15330338211036233
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of MITD1 and Associates With Immune Infiltration in Kidney Renal Clear Cell Carcinoma

Abstract: Kidney renal clear cell carcinoma (KIRC) is one of the most malignant diseases with poor survival rate over the world. The tumor microenvironment (TME) is highly related to the oncogenesis, development, and prognosis of KIRC. Thus, making the identification of KIRC biomarkers and immune infiltrates critically important. Microtubule Interacting and Trafficking Domain containing 1(MITD1) was reported to participate in cytokinesis of cell division. In the present study, multiple bioinformatics tools and databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Nonetheless, a few studies have revealed that MITD1 plays multiple roles in the progression of various cancers. MITD1 may serve as a biomarker for LIHC and KIRC [ 11 , 14 ]. MITD1 might also inhibit the migration of BLCA cells [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, a few studies have revealed that MITD1 plays multiple roles in the progression of various cancers. MITD1 may serve as a biomarker for LIHC and KIRC [ 11 , 14 ]. MITD1 might also inhibit the migration of BLCA cells [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of MITD1 leads to instability of the midbody and abscission failure, and the depletion of MITD1 leads to increased blebbing and premature abscission in cells [ 6 ]. ESCRT-III plays a critical role in several cancers, such as pancreatic tumors [ 8 ], prostate cancer [ 9 ], ovarian cancer [ 10 ], kidney renal clear cell carcinoma [ 11 , 12 ], bladder cancer [ 13 ], and liver cancer [ 14 ]. Moreover, disorders of abscission in cytokinesis can cause genomic instability and tumorigenesis [ 15 ], implying the existence of a network of interactions between MITD1 and the tumor microenvironment (TME), microsatellite instability (MSI), tumor mutational burden (TMB), homologous recombination deficiency (HRD), and ploidy.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the 5-year disease-specific survival rate of patients with RCC stage IV is less than 10% [2]. KIRC is the main subtype of RCC, with the highest incidence, accounting for about 80% of all RCCs.…”
Section: Introductionmentioning
confidence: 99%